2010
DOI: 10.1021/nn1000222
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanobubbles as Transient Vapor Nanobubbles Generated around Plasmonic Nanoparticles

Abstract: We have used short laser pulses to generate transient vapor nanobubbles around plasmonic nanoparticles. The photothermal, mechanical and optical properties of such bubbles were found to be different from those of plasmonic nanoparticle and vapor bubbles as well. This phenomena was considered as a new complex nanosystem -plasmonic nanobubble (PNB). Mechanical and optical scattering properties of PNB depended upon the nanoparticle surface and heat capacity, clusterization state, and the optical pulse length. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
484
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(502 citation statements)
references
References 80 publications
17
484
1
Order By: Relevance
“…16 Several experimental and numerical approaches aimed at studying the internal processes of heat generation under pulsed illumination and the subsequent effects observed in the surrounding medium, e.g. temperature and pressure variations, [17][18][19] acoustic wave generation, 18 vibration modes, [20][21][22] , cell apoptosis, 11 drug release 9,23 nanosurgery, 15,24 bubble formation, [25][26][27][28] NP shape modification 29 and melting, [29][30][31] nanosecondpulses for biomedical applications, 32,33 extreme thermodynamics conditions. [33][34][35][36][37] In this paper, we present and use a versatile numerical framework to investigate theoretically and numerically the evolution of the temperature distribution of a gold nanoparticle immersed in water when shined by a femtosecond-pulsed laser.…”
Section: 10mentioning
confidence: 99%
“…16 Several experimental and numerical approaches aimed at studying the internal processes of heat generation under pulsed illumination and the subsequent effects observed in the surrounding medium, e.g. temperature and pressure variations, [17][18][19] acoustic wave generation, 18 vibration modes, [20][21][22] , cell apoptosis, 11 drug release 9,23 nanosurgery, 15,24 bubble formation, [25][26][27][28] NP shape modification 29 and melting, [29][30][31] nanosecondpulses for biomedical applications, 32,33 extreme thermodynamics conditions. [33][34][35][36][37] In this paper, we present and use a versatile numerical framework to investigate theoretically and numerically the evolution of the temperature distribution of a gold nanoparticle immersed in water when shined by a femtosecond-pulsed laser.…”
Section: 10mentioning
confidence: 99%
“…The calculated steam generation efficiency reached 80%, meaning only 20% of the solar radiation was used to increase the bulk fluid temperature. Later simulation work [44][45][46] showed the possibility of nanobubble formation based on a non-equilibrium phase change assumption.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the steam generation mechanism is concerned, it has been shown analytically that a minimum radiation flux of 3×10 8 W/m 2 is required to produce nanobubbles on heated nanoparticles [46,49,50], which can only be reached by powerful laser beams. In a separated study, Julien et al [51] showed that 1×10 10 W/m 2 was required to generate a nanobubble on a plasmonic gold nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter involved in heat generation is the power of the operating laser as well as whether the laser is run in continuous wave (CW) or pulsed wave (PW) mode when interacting with nanoparticles [150,[159][160][161][162][163]. While there is still some debate as to which mode is best, pulsed mode is generally considered more efficient than continuous mode for heating nanoparticles in photothermal applications [150,[164][165][166][167][168].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 99%